Comparison of potentiation post-activation responses in two dominant hip strength exercises - Vargas-Molina, S.; Petro, J. L.; Castro, N.; Carbone, L.; Bonilla, D.-A.; Chulvi-Medrano, I.; Benitez-Porres, J. (BASES Conference 2019, 2019)
Positive potentiation post-activation (PAP) responses inbroad jump (BJ)has been reported in rugby players after box squat alternated with standing broad jumps (Seitz et al., 2016). However, use of back squat didnot generate PAP in vertical jump in comparison to hex-bar deadlift (DL)(Scott et al., 2017). Therefore, it is important to evaluate which movement derived from resistance exercise is more similar to BJ and possibly would generate an specific PAP response. The aim of this study was to evaluate the effect of an anterior-posterior movement (hip thrust [HT]) on PAPlevels by BJ, in comparison to an axial-component exercise (DL). Fifteenresistance-trained rugby players participated in this study (age, 22.7 ± 1.6;body weight, 89.9 ± 10.6; height, 181.8 ± 6.5; BMI, 27.2 ± 2.3;1RM DL1RM, 117 ± 20.6; 1RM HT, 133.3 ± 21.5. Subjects attended four sessions to the laboratory with seven days between each session. Anthropometric measurements and one-repetition maximum (1-RM) estimations for HTand DL (grip width 72 cm) were performed in the first and third sessions,while PAP tests for both exercise protocols were performed during the second and fourth sessions (subjects performed two repetitions at 90% 1-RM with 8 minutes of recovery between HT and DL exercises, and then theBJ was performed). Data were analyzed by a general lineal model (GLM)with repeated measures and a delta analysis (? = post - pre) was performed to determine the 95% confidence interval (95% CI)for themean. The GLM showed both significant difference and large effect size onBJ per Time [pre vs. post] (P> 0.001; ?p2= 0.990), but no differences onTime x Protocol interaction (P= 0.452; ?p2=0.020) or per Group (0.748; ?p2= 0.004) were found. There were significant changes [X ± SD, CIs 95%] on BJafter HT (5.2±5.6, 2.1-8.3;P= 0.03) and DL (6.9±5.3, 4.0-9.9:P< 0.001);however, no difference was found between the exercise protocols (P=0.748). Our results suggest that DL and HP provided with large effects on PAP to improve the BJ outcomes, but there was no difference between these exercises.